Associations of long-term exposure to ambient air pollution with cardiac conduction abnormalities in Chinese adults: The CHCN-BTH cohort study. (October 2020) - Cao, Han; Li, Bingxiao; Peng, Wenjuan; Pan, Li; Cui, Ze; Zhao, Wei; Zhang, Han; Tang, Naijun; Niu, Kaijun; Sun, Jixin; Han, Xiaoyan; Wang, Zhengfang; et al.
Highlights: Long-term air pollutant exposures may contribute to cardiac conduction abnormalities. PM2.5 may be the most stable pollutant reflecting the associations. People with specific characteristics are more susceptible to the adverse effects. Abstract: Background: Evidence regarding the effects of long-term and high-level ambient air pollution exposure on cardiac conduction systems remains sparse. Objectives: To investigate the associations of long-term exposure to air pollution and cardiac conduction abnormalities in Chinese adults and explore the susceptibility characteristics. Methods: In 2017, a total of 27, 047 participants aged 18–80 years were recruited from the baseline survey of the Cohort Study on Chronic Disease of Communities Natural Population in Beijing, Tianjin and Hebei (CHCN-BTH). The three year (2014–2016) average pollutant concentrations were assessed by a spatial statistical model for PM2.5 and air monitoring stations for PM10, SO2, NO2, O3 and CO. Residential proximity to a roadway was calculated by neighborhood analysis. Associations were estimated by two-level generalized linear mixed models. Stratified analyses related to demographic characteristics, health behaviors, and cardiometabolic risk factors were performed. Two-pollutant models were used to evaluate the possible role of single pollutants. Results: We detected significant associations of long-term air pollutant exposure with increased heart rate (HR), QRS and QTc, such that an interquartile range increase in PM2.5 was associated with 3.63% (95% CI: 3.07%, 4.19%), 1.21% (95% CI: 0.83%, 1.60%), and 0.13% (95% CI: 0.07%, 0.18%) changes in HR, QRS and QTc, respectively. Compared to the other pollutants, the estimates of PM2.5 remained the most stable across all two-pollutant models. Similarly, significant associations were observed between living closer to a major roadway and higher HR, QRS and QTc. Stratified analyses showed generally greater association estimates in older people, males, smokers, alcohol drinkers, and those with obesity, hypertension and diabetes. Conclusions: Long-term exposure to ambient air pollution was associated with cardiac conduction abnormalities in Chinese adults, especially in older people, males, smokers, alcohol drinkers, and those with cardiometabolic risk factors. PM2.5 may be the most stable pollutant to reflect the associations.